2018
DOI: 10.1177/1533033818805715
|View full text |Cite
|
Sign up to set email alerts
|

Can “Indirect” Contact Laser Surgery be Used for Fluorescence-Image Guided Tumor Resections? Preliminary Results

Abstract: Ensuring the complete removal of tumor tissue is the main challenge during resection operations. Recently, a technique of “indirect” contact laser surgery has been developed. In this study we assess the possibility of using such surgery for fluorescence image-guided tumor resection. Mouse colon adenocarcinoma CT-26 cells stably expressing the fluorescent protein mKate-2 was used as the tumor model. Resections of the tumor nodes were performed with either a scalpel blade, a laser scalpel with a bare tip, or a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In our previous study, we demonstrated a high efficiency of employing a laser scalpel instead of a cold knife in preventing tumor recurrence [ 38 ], while the aim of this study was to evaluate the additional effect of a complementary PDT procedure on the tumor bed after surgical treatment. As demonstrated earlier, the use of a laser scalpel results in the formation of a caramelization layer [ 39 ] on the tissue surface, the parameters of which are described in other papers [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we demonstrated a high efficiency of employing a laser scalpel instead of a cold knife in preventing tumor recurrence [ 38 ], while the aim of this study was to evaluate the additional effect of a complementary PDT procedure on the tumor bed after surgical treatment. As demonstrated earlier, the use of a laser scalpel results in the formation of a caramelization layer [ 39 ] on the tissue surface, the parameters of which are described in other papers [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%